Analyzing Good Budget Management Principles at the General Election Commission - Zainuri, Ahmad (International Journal Labs, 2023)
Background: With the demand for good budget management, the role of the Cilegon City KPU (General Election Commission) budget manager requires competence in managing it, and requires an understanding of the duties, functions, and position of each budget manager official called as payment instrument official. Aim: This research aims to examine the implementation of budget management principles at the Cilegon City KPU, the constraints and the efforts to overcome the constraints. Methods: This research employed a descriptive qualitative method. The data were collected through interviews, observations and document reviews. Findings: The information on budget management was still limited and in the form of a written report. The budget implementation was not efficient because the realization of some activities was not in accordance with their objectives and did not state any priority to be accomplished. The budget setting procedures were still top-down and determined directly by the National Election Commission. Some changes in the budget and activities were not revised in the final report on election activities and the budget did not fully accommodate the needs of all polling stations (TPS). Some procurement of goods and services and other facilities did not have clear evidence of transactions and some of them were unrealistic and did not correspond to the market price. Not all stakeholders (Local Representatives, DPPKD, PPK, PPS and community leaders) were involved in the preparation, implementation and discussion on the electoral budget accountability report.